Effect Company Size, Age Of Company, Islamic Corporate Social Responsibility On Earning Coeficient Response - Novianto Noegroho; Adhi Widyakto; RR Lulus Prapti NSS (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Islamic Corporate Social Responsibility is the reporting of corporate social responsibility with sharia principles. The disclosure of social responsibility must be in accordance with the values of the concept of Maqashid Shari'ah. For sharia-based companies, use Islamic Social Reporting in reporting corporate social responsibility. All implementation of social responsibility that has been carried out by the company will be made public through social disclosure in the annual report issued by the company. This research aims to find out the influence of company size, age of the company and investment account holders on disclosure of Islamic corporate social responsibility. The population in this study was an Islamic commercial bank registered with the Financial Services Authority using purposive sampling techniques. The analytical technique in this study is regression of panel data. The results of this study showed that the size of the company, the age of the company and Islamic Corporate Social Responsibility influence simultaneously on the disclosure of Islamic corporate social responsibility. Partially, the size of the company positively influences the disclosure of Coeficient Response Earnings, while the company's lifespan and islamic corporate social responsibility have no effect on the disclosure of Coeficient Response Earnings.